Peran resiliensi keluarga dalam perkembangan konsep diri remaja - Ahmad, Masnaeni; Pulungan, Zulhaini Sartika A.; Hardiyati (JURNAL KESEHATAN PRIMER, 2023)
Introduction:  Self-concept is formed from social contacts and experiences with other people from time to time so the family plays a very important role in shaping the adolescent's self-concept. This study aims to determine the role of family resilience on adolescent self-concept. Methods: This research is a cross-sectional correlational descriptive study. The population in this study consisted of 3084 Mamuju City junior high school students. A total of 354 students and their families were selected using stratified random sampling. The Family Resilience Assessment Scale (FRAS) is utilized to assess family resilience, while the Tennessee Self Concept Scale (TSCS) is used to assess adolescent self-concept. Results:  The findings of testing hypotheses by the Spearman Rank correlation technique showed a significant connection between family resilience and teenage self-concept (p=0.000). Family resilience carries a 44.5% effect on teenage self-concept. Family resilience has a vital role in shaping the formation of teenage self-concept. Conclusion:  Adolescent self-concept is likely to be developed within families that function ideally. It happens due to the adolescent's self-concept forming in sync with their family experience.